Analisis cerita rakyat Malin Kundang dengan teori naratologi A.J. Greimas - Husna, Lativa (Maliki Interdisciplinary Journal, 2026)
This research analyzes the Indonesian folklore "Malin Kundang" using A.J. Greimas’s narratology theory to identify its actantial scheme, the function of each actant, and its narrative functional model. "Malin Kundang" is a rich cultural heritage embodying significant moral values. A qualitative descriptive method was employed, with data collected through reading and note-taking techniques from the narrative text. The analysis reveals that the story’s structure can be comprehensively understood through Greimas’s six actants: Malin Kundang as the subject who initially struggles against poverty (sender) to achieve wealth (object), aided by his hard work (helper). However, his success leads to arrogance (internal opponent) and subsequently the rejection of his mother (external opponent), culminating in his transformation into stone. The wider community serves as the receiver of the strong moral message about filial piety and the consequences of disobedience. The story’s functional model follows an initial situation marked by poverty, a transformation phase encompassing the competence test, the acquisition of the object, and the glorious test (the climax of the mother’s rejection), leading to a tragic final situation imbued with moral lessons. This study affirms the effectiveness of Greimas’s theory in uncovering the underlying structure and didactic messages within folklore.